2019
DOI: 10.1186/s12913-019-3998-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of service quality from patients’ viewpoint

Abstract: BackgroundMeasuring patients’ perception from health service quality as an important element in the assessment of service quality has attracted much attention in recent years. Therefore, this study was conducted to find out how the patients evaluated service quality of clinics at teaching hospitals affiliated with Tehran University of Medical Sciences in Iran.MethodsThis cross-sectional study was conducted in Tehran in 2017 and 400 patients were randomly selected from four hospitals. Data were collected using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
3
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 30 publications
6
62
3
6
Order By: Relevance
“…Poor doctor-patient communication affects overall medical care (4,5,22,30), but in the case of Kazakhstan we have revealed that miscommunication is just one of the factors affecting doctor-patient interactions. From 2017 to 2018, all medical schools in Kazakhstan implemented "Communication skills" as a separate and mandatory course in the medical curriculum (34).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Poor doctor-patient communication affects overall medical care (4,5,22,30), but in the case of Kazakhstan we have revealed that miscommunication is just one of the factors affecting doctor-patient interactions. From 2017 to 2018, all medical schools in Kazakhstan implemented "Communication skills" as a separate and mandatory course in the medical curriculum (34).…”
Section: Discussionmentioning
confidence: 88%
“…Patient perceptions of the physician consultation, provision of information to patients and the environment of delivering services are what determine the patient's perception of quality of services in clinics (1,22). For patients, the process and quality of interactions with health professionals had more signi cant effects on the patients' perceived value rather than environmental features of quality of service delivery which had no signi cant effect on perceived value or overall satisfaction (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…A questionnaire was completed Data were analyzed by SPSS 23. After the descriptive tests, linear regression analysis was applied to measure the effect of service quality variables and demographic characteristics on patient satisfaction (22).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies link patient satisfaction and the perception of quality with state-of-the-art equipment and modern technologies in medical facilities [7,14,16]. However, other studies show that new technologies and equipment are not necessarily the key to delivering patient-centered care or even in gaining patient satisfaction [9,10,12]. Organizational influences that determine emphases on the use of technology and other factors in patient-centered care include policies, resources, social norms, managerial commitment, training programs, and employee empowerment.…”
Section: Introductionmentioning
confidence: 99%